ETNOMEDISIN TUMBUHAN SUNGKAI (Peronema canescens) OLEH SUKU DAYAK DAN SUKU BANJAR DI KALIMANTAN TENGAH - Sasi Gendro Sari; Rimaa Rahmawati; Rusmiati Rusmiati; Susi Susi (Universitas Lambung Mangkurat, 2023)
Sungkai Peronema canescens is well known as a medicinal plant at Central Kalimantan. Indiginous people of Dayak and Banjar tribes who are living in East Kotawaringin Regency consume Sungkai plant into traditional medicine. The potential use of sungkai as medicine was identified from three selected villages of East Kotawaringin Regency namely Bagendang Permai, Bagendang Hulu and Bagendang Hilir. Ethnomedicine of sungkai leaves was investigated using a semi structured questionnaire technique and 180 respondents were selected by a purposive sampling. The interviewees were divided into gender and four groups based on their ages to identify knowledge level in using sungkai leaves as a medicinal plant. Their knowledge was analyzed based on gender and ages using Kruskal Wallis test and then Mann Whitney U-test was used to decide the difference of knowledge level. The results showed leaves are the main part to be utilized as medicine. Leaves were preferably boiled by respondents to increase their immune system and to cure fever and some used for puerperal mother bath mixture. The indiginous knowledge level was 82.57 categorized as a high knowledge level. Moreover, both gender and ages had no difference knowledge level on using sungkai as medicine.